The Abbasid Era and the Dynamics of Medical Science - Moch. Said; Ajeng Dwi Fatmawati; Muhammad Amiruddin (Yayasan Adra Karima Hubbi, 2025)
The peak of the glory of Islam can be seen from the progress of the Abbasid Dynasty during the leadership of Harun Ar-Rasyid. Because of the rapid progress in all fields, this era was nicknamed as The Golden Age (Golden Age). This progress is seen in various fields ranging from education, economy and infrastructure, making the Abbasid Dynasty highly respected by other nations. Progress is also seen in the field of health and the development of medical science. The Abbasid Dynasty government focused on developing science so that Muslim scientists and Muslim doctors emerged whose knowledge influenced the world of medicine in the world. Starting from Ibn Sina and Ar-Razi who are very famous as the fathers of modern medicine. The purpose of writing this article is to find out the development and progress of the Abbasid Dynasty in the field of medicine and health. The process of making this article uses the (Library Research) method by collecting a number of books, magazines, journals and relevant sources as well as in-depth analysis. Medical science developed rapidly in the Abbasid era where medical figures and techniques emerged that were very influential for the development of medical science and technology today. Ibn Sina became a pioneer in the advancement of health and medical science, he also wrote a book At-Tibb Law which is a reference for medical science throughout the world.